A Case Report of Possibly Related Acute Generalized Exanthematous Pustulosis with Staphylococcus pettenkoferi - Wang S; Bai J; Qiao J (Dove Medical Press, 2023)
Su Wang, Juan Bai, Jianjun Qiao Department of Dermatology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People's Republic of ChinaCorrespondence: Jianjun Qiao; Juan Bai, Email qiaojianjun@zju.edu.cn; 1515033@zju.edu.cnAbstract: Acute generalized exanthematous pustulosis (AGEP), an uncommon severe cutaneous adverse reaction, is believed to be a T cell-mediated hypersensitivity reaction, of which the most common cause is medication. However, infections have also been reported to be associated with AGEP. Here, we present a case of AGEP possibly related with Staphylococcus pettenkoferi.Keywords: acute generalized exanthematous pustulosis, Staphylococcus pettenkoferi